Pigmented Ependymoma of the Fourth Ventricle—A Curious Entity: Report of a Rare Case With Review of Literature. (February 2021) - Malhotra, Ankit; Rao, Shilpa; Santhoshkumar, Rashmi; Muralidharan, Nufina; Mitra, Saikat; Shetty, Sathwik
A 16-year-old boy presented with a tumor located in fourth ventricle, which showed histological features of an ependymoma replete with perivascular pseudorosettes and true ependymal rosettes. Interestingly, many of the tumor cells exhibited abundant cytoplasm stuffed with a grayish brown pigment. Histochemical stains showed the pigment to be acid fast and periodic acid–Schiff positive and negative for Masson-Fontana melanin stain. Additionally, the pigment displayed brilliant autofluorescence under ultraviolet light of a fluorescent microscope. Ultrastructure examination of the pigment revealed a non–membrane-bound biphasic structure with an electron-dense core and electron-lucent periphery. Only few similar case reports mention such pigmented ependymomas to contain a mixture of neuromelanin and lipofuscin while others mention it to be melanin itself. Our workup suggests the pigment to represent lipofuscin or its derivative. Generally known to be a pigment of wear and tear, the significance of finding it in a tumor with such abundance remains to be understood and explored.